2013
DOI: 10.1155/2013/719306
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural Characteristics and Mechanical Properties of Friction Stir Spot Welded 2A12-T4 Aluminum Alloy

Abstract: 2A12-T4 aluminum alloy was friction stir spot welded, and the microstructural characteristics and mechanical properties of the joints were investigated. A softened microstructural region existed in the joint, and it consisted of stir zone (SZ), thermal mechanically affected zone (TMAZ), and heat affected zone (HAZ). The minimum hardness was located in TMAZ, and the average hardness value in SZ can be improved by appropriately increasing welding heat input. The area of complete bonding region at the interface i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…Figure 10 showing the result of the hardness test revealed that the zone affected by the heat from the welding changed its hardness especially in the zone obtained the heat from tool shoulder resulting in significantly increasing hardness [33]. However, the mechanism of hardness change around the welding zone from FSSW was also caused by density of the alloy after stirring, cooling rate after welding, residual stress and the change of heat during the welding [34]. The highest hardness obtained from the test had the average value of 79.83 HV in the weld zone and 115.18 HV in the heat affected zone, whereas the original of SSM 7075 aluminum alloy had the average value of 99 HV.…”
Section: Hardness Testmentioning
confidence: 99%
“…Figure 10 showing the result of the hardness test revealed that the zone affected by the heat from the welding changed its hardness especially in the zone obtained the heat from tool shoulder resulting in significantly increasing hardness [33]. However, the mechanism of hardness change around the welding zone from FSSW was also caused by density of the alloy after stirring, cooling rate after welding, residual stress and the change of heat during the welding [34]. The highest hardness obtained from the test had the average value of 79.83 HV in the weld zone and 115.18 HV in the heat affected zone, whereas the original of SSM 7075 aluminum alloy had the average value of 99 HV.…”
Section: Hardness Testmentioning
confidence: 99%
“…Welding parameters (see Fig. 2a) which have a strong impact on the joint strength during FSSW include pin profile, tool rotation rate, dwell time, plunge rate, shoulder depth and axial force [13]. Various distinctions are produced by the tool penetration and the dwell time; the heat generated during the FSSW process, how the material plastically deforms around the pin and the weld geometry; which evidently has an influence on the mechanical properties of the spot welds [14].…”
Section: Effect Of Different Fssw Process Parametersmentioning
confidence: 99%
“…The tool rotation speed was change from 710 rpm to 1800 rpm. Figure (13) and (14) shows the spindle speed against average tensile shear load at different dwell time (10, 15 sec). For each parameter used, five specimens were tested, and the standard-deviation was usually less than 12 % of the average load value.…”
Section: Effect Of Tool Rotational Speedmentioning
confidence: 99%
“…Found a softened micro-structural area found in the joint, and it consisted of (SZ) stir-zone, (TMAZ)thermal mechanically affectedzone and (HAZ)heat affected-zone, also record minimum value of hardness in the region of TMAZ and the maximum of hardness in the region of SZ because increasing welding heat input. The tensile shear load of the weld increased with increasing rotation of tool speed, but it decreased with decreasing shoulder plunging depth or increasing plunge rate [14]. Sun et al in (2013) welded AA6061-T6 with mild steel sheets at (1mm) of thickness by using friction spot welding process.…”
Section: Introductionmentioning
confidence: 99%